2020
DOI: 10.1038/s41598-020-67452-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of environmental DNA in cultivated soils: implication of this memory effect for reconstructing the dynamics of land use and cover changes

Abstract: eDnA refers to DnA extracted from an environmental sample with the goal of identifying the occurrence of past or current biological communities in aquatic and terrestrial environments. However, there is currently a lack of knowledge regarding the soil memory effect and its potential impact on lake sediment eDnA records. to investigate this issue, two contrasted sites located in cultivated environments in France were studied. In the first site, soil samples were collected (n = 30) in plots for which the crop ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 42 publications
(44 reference statements)
0
37
0
Order By: Relevance
“…PCR replicability was calculated as the mean proportion of detections in PCR replicates across all taxa within a sample. from grapevine are still detected in high quantity despite the crop already being strongly decreased 60 years ago [302]. The frequency of positive PCRs and the detection probability of domestic mammals was significantly higher with the Amicons (AmTaberlet2012 method), confirming their usefulness.…”
Section: Methodsmentioning
confidence: 88%
“…PCR replicability was calculated as the mean proportion of detections in PCR replicates across all taxa within a sample. from grapevine are still detected in high quantity despite the crop already being strongly decreased 60 years ago [302]. The frequency of positive PCRs and the detection probability of domestic mammals was significantly higher with the Amicons (AmTaberlet2012 method), confirming their usefulness.…”
Section: Methodsmentioning
confidence: 88%
“…A significant proportion of the most productive soils around the world are found under these conditions, and this situation strengthens the need to develop new approaches to discriminate between these land use-based sources. Alternative tracers such as environmental DNA (Foucher et al, 2020) and compound specific stable isotopes (CSSI) (Blake et al, 2012) may provide a powerful alternative to trace the contribution of specific land use sources to sediment. However, technical solutions allowing for the global application of these methods still need to be developed (Brandt et al, 2018;.…”
Section: Mixing Model Resultsmentioning
confidence: 99%
“…A recent study by Foucher et al . 49 showed that eDNA cultivated at 20–30 cm underground might remain for 6 or 7 years. Our results showed that the persistence time scale of eDNA at the soil surface was relatively shorter, possibly because the absorption of soil particles, weathering, and UV effects at the soil surface may have promoted DNA degradation.…”
Section: Discussionmentioning
confidence: 99%